Characteristic of Video Clips of Preservice Mathematics Teachers Ability to Notice - Liza Indriyani; Rahmah Johar; Cut Morina Zubainur; Hannah-Charis O. Walker (Didaktik Matematika, 2024)
Noticing is the teacher's ability to pay attention to critical moments during learning. The noticing ability of preservice mathematics teachers can be trained by watching video recordings of teaching practices. However, there are limited video clips that can be used as teaching materials to develop the noticing abilities of preservice mathematics teachers. Therefore, this study aims to identify the characteristic of preservice mathematics teachers ability to notice. Video clips consist of a series of significant moments to observe. This research used a survey of moments in video recordings of preservice mathematics teachers when noticing their students' thinking in the learning process. The data analysis was based on learning video clips, containing the complexity of noticing problems related to the preservice mathematics teachers ability. The results indicated that the identified video clips, recordings of classroom interactions, featured teacher activities such as asking, guiding, responding, and assisting students. However, the preservice teachers demonstrated a low ability to notice, particularly in the interpreting and shaping aspects. These video clips, specifically those that highlight these teacher activities, can be utilized as learning tools in teacher development programs to enhance preservice teachers' noticing skills, especially in interpreting and shaping aspects.